Manajemen Pengelolaan Sampah Di Kota Kendari (Studi Pada Dinas Lingkungan Hidup Dan Kehutanan Kota Kendari) - Yunus, Muhammad; Kadir, Abdul; Batara, Suriyani Bunga (Universitas Halu Oleo, 2020)
The aim of this research to know and describe the Waste Management implemented by the Kendari City Environment and Forestry Service with The research method used is descriptive qualitative, a description of the results of observations, interviews and documentation studies, the data that has been obtained will be analyzed qualitatively and described in descriptive form. The results showed that The implementation of the management function at the Kendari City Environment and Forestry Service has been carried out well. This is indicated by a good planning function where organizational goals are clearly stated in the vision and mission, then the organizational function is in a good category where the division of employee work is carried out clearly and the implementation of employee work is in accordance with the division of labor, then the movement function is in a good category where employees are able to work independently and employees work optimally, and finally the supervisory function is in the good enough category where the supervision carried out needs to be carried out continuously. Waste management in Kendari city itself is carried out with several principles carried out at the Puuwatu TPA in terms of the first waste management, namely the use of organic and non-organic waste. Second, the use of organic waste is used as the newest source of electrical energy, the third is the use of methane gas, and the fourth is the use of waste into compost.